Ankylosing spondylitis and kinesiophobia - Ugur Ertem (PeerJ)
Background Ankylosing spondylitis (AS) is a chronic rheumatic disease that predominantly affects the axial skeleton, causing pain and functional impairment. Kinesiophobia, or fear of movement, is common in patients with chronic pain conditions and can significantly hinder treatment outcomes. This study aims to assess the level of kinesiophobia in AS patients and explore its relationship with demographic characteristics, disease duration, pain intensity, disease activity, and functional impairment. Methods This single-center study included 35 AS patients from July 2021 to July 2023. Patient demographics, disease duration, disease activity (BASDAI (Bath Ankylosing Spondylitis Disease Activity Index)), functionality (BASFI (Bath Ankylosing Spondylitis Functional Index)), pain intensity (VAS (Visual Analog Scale)), and kinesiophobia (TSK (Tampa Scale of Kinesiophobia)) were recorded and analyzed. Patients were categorized into low and high kinesiophobia groups based on TSK scores. Results Of the 35 AS patients, 15 (42.86%) had high kinesiophobia levels (TSK ≥37). Patients with high kinesiophobia had significantly higher BASDAI, BASFI, and VAS scores (p < 0.001) compared to those with low kinesiophobia. No significant relationship was found between kinesiophobia and age, gender, or disease duration (p > 0.05). Conclusion High levels of kinesiophobia in AS patients are associated with increased pain, disease activity, and functional impairment. Early interventions targeting kinesiophobia could improve treatment outcomes and patient functionality.